2017
DOI: 10.3390/molecules23010007
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-Induced Changes in MicroRNA Expression in Primary Human Fibroblasts Harboring Carnitine-Palmitoyl Transferase-2 Gene Mutation, Leading to Fatty Acid Oxidation Deficiency

Abstract: Carnitine palmitoyltransferase-2 (CPT2) is a mitochondrial enzyme involved in long-chain fatty acid entry into mitochondria for their β-oxidation and energy production. Two phenotypes are associated with the extremely reduced CPT2 activity in genetically deficient patients: neonatal lethality or, in milder forms, myopathy. Resveratrol (RSV) is a phytophenol produced by grape plant in response to biotic or abiotic stresses that displays anti-oxidant properties, in particular through AP-1, NFκB, STAT-3, and COX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…While we previously identified RSV-dependent miRNA modulation in THP-1 macrophages [3], here we report changes in miRNA expression linked to CPT2-deficiency. We also identified miRNAs whose expression changed following RSV treatment of control or CPT2-deficient fibroblasts isolated from patients [4]. We found that miR-378 was down-regulated by RSV in control fibroblasts.…”
Section: Resultsmentioning
confidence: 84%
“…While we previously identified RSV-dependent miRNA modulation in THP-1 macrophages [3], here we report changes in miRNA expression linked to CPT2-deficiency. We also identified miRNAs whose expression changed following RSV treatment of control or CPT2-deficient fibroblasts isolated from patients [4]. We found that miR-378 was down-regulated by RSV in control fibroblasts.…”
Section: Resultsmentioning
confidence: 84%
“…In primary human fibroblasts, resveratrol was able decrease miR-566 and miR-23a, restoring mitochondrial fatty acid β-oxidation rates in primary human fibroblasts form patients harboring carnitine palmitoyltransferase-2 mutation associated with two different phenotypes (neonatal lethality or myopathy in mild forms) [120]. Therefore, resveratrol, independently of the disease, led to miR-566 and miR-23a modulation specifically [120]. Microarray analysis showed that human THP-1 monocytic cells treated with resveratrol increased the expression of miR-663 decreasing miR-155 [121].…”
Section: Resveratrol and Micrornasmentioning
confidence: 98%
“…These compounds have been the subject of numerous studies over the last two decades. Thirteen research and review articles have been published in this special issue: four articles concern the biosynthesis of phytoalexins as a response to biotic and/or abiotic elicitors capable of inducing their production in plants [ 1 , 2 , 3 , 4 ], two articles describe methods for phytoalexin analysis in complex matrices [ 5 , 6 ], one article reports on phytoalexin metabolism by fungi [ 7 ], and six articles focus on the biological activity of phytoalexins [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%
“…Beside their antifungal properties in plants, phytoalexins show preventing activities against human diseases as antioxidant, anticancer, cardioprotective, antibacterial, and antifungal agents. Six articles report here on the biological implication of phytoalexins in human diseases [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation